REKONSTRUKSI PEMANFAATAN LAHAN SEKOLAH MELALUI PROGRAM KEBUN KETAHANAN PANGAN SEBAGAI UPAYA PENGUATAN EKOSISTEM PENDIDIKAN BERKELANJUTAN DI SDN KERTAJAYA IV/210 - Rara Sagita Nur Fajar; Dzakiyah Risya Rahmah; Maychellina Azatyl Syafina; Eka Sefia Rahma Avida; Agastya Bisma Putra Nawawi; Wiwid Safitri Nofitasari; Putra Anugra Maulana; Gibron Amirul Haq; Poltjes Pattipeilohy; Patmawati (STKIP Subang, 2026)
Optimizing school land is an effective strategy to create a productive learning environment while supporting sustainable education. The Food Security Garden Program, implemented through the Surabaya Mengajar Program (PSM) 9.0 at SDN Kertajaya IV/210, aimed to transform underutilized school land into a productive garden with educational and ecological value. This study employed a descriptive qualitative approach using observation, documentation, and reflection as data collection techniques. The program included needs assessment, planning, garden arrangement, planting food crops, maintenance, monitoring, and evaluation. The results showed that the unused land was successfully reconstructed into a well-organized Food Security Garden based on plant zoning while utilizing recycled plastic bottles and used water containers as planting pots. The program improved the school environment and provided authentic learning experiences for university students by enhancing their pedagogical, managerial, leadership, professional communication, and problem-solving skills. Overall, the program contributed to optimizing school resources and strengthening the implementation of sustainable education.